Demonstrating the clinical utility of genomic profiling using cerebrospinal fluid to inform management of central nervous system tumors – a meta analysis of the literature - Sakshi Khurana; Qian Nie; Kala F. Schilter; Honey V. Reddi (The Journal of Liquid Biopsy, 2025)
Purpose: Meta-analysis of literature was performed to gain an understanding of the performance of genomic profiling assays in cerebrospinal fluid (CSF) for the diagnosis and management of CNS cancers. Methods: Using PRISMA methodology, PubMed was searched with the following search terms; “CSF and liquid biopsy” and “cerebrospinal fluid, liquid biopsy, mutations.” Key data fields such as DNA input, technologies used, biomarkers evaluated, types of CNS tumors, sensitivity and specificity, and performance outcomes were analyzed. Studies were excluded if they did not evaluate cancer, use CSF or molecular test methods, had <10 patients, involved pediatric cases or were review articles. Results: A total of 63 studies were included in the analysis with a majority using ctDNA (n = 38) and targeted NGS panels (n = 45) with both sensitivity and specificity being reported in 24 studies. Of the samples sequenced, 76 % of the primary cancers were gliomas with lung cancer making up 67 % of the metastatic cancers. The Belay Summit™ test performed significantly better in both primary and metastatic CNS cancers with 88 % and 95 % sensitivity respectively compared to studies that used NGS with 6 of the 24 demonstrating a median sensitivity of 47 ± 1.95 % for primary and 7 of 24 demonstrating a median sensitivity of 71 ± 0.76 % for metastatic cancers. Conclusions: CSF does have potential to inform treatment and management of CNS tumors. For a CSF based molecular test to be highly sensitive and specific, key considerations include panel content, methodology used, the type of variants being evaluated and the inclusion of true negative controls.